2002
DOI: 10.1046/j.1440-1819.2002.01062.x
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic consideration of Morita shinkeishitsu and DSM‐III‐R

Abstract: The purpose of the present study was to empirically and objectively clarify the diagnostic standing of Morita shinkeishitsu, the subject of Morita therapy, by comparing and contrasting it with the operational diagnosis of the Diagnostic and Statistical Manual of Mental Disorders (3rd edition, revised; DSM-III-R). Morita therapists' clinical diagnoses of 88 outpatients who requested Morita therapy were compared with the results of the independently conducted operational diagnoses (structured clinical interview … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 2 publications
0
13
0
Order By: Relevance
“…In the West, the onset of social phobia is reported in the majority of cases before the age of 18 (Otto et al, 2001). Cultural factors influencing social phobia have been of particular interest to researchers worldwide (Okano, 1994;AlKhodair and Freeman, 1997;Chang, 1997;Heimberg et al, 1997;Kitanishi et al, 2002;Abdel-Khalek and Al-Damaty, 2003). Although studies from developing countries have generally shown a low prevalence of SAD (McIlvenny et al, 2000;Ono et al, 2002), in East Asia reports have revealed a social anxiety-like condition marked with fear of distress, and even fear of harming others (Chang, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…In the West, the onset of social phobia is reported in the majority of cases before the age of 18 (Otto et al, 2001). Cultural factors influencing social phobia have been of particular interest to researchers worldwide (Okano, 1994;AlKhodair and Freeman, 1997;Chang, 1997;Heimberg et al, 1997;Kitanishi et al, 2002;Abdel-Khalek and Al-Damaty, 2003). Although studies from developing countries have generally shown a low prevalence of SAD (McIlvenny et al, 2000;Ono et al, 2002), in East Asia reports have revealed a social anxiety-like condition marked with fear of distress, and even fear of harming others (Chang, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Morita found the shared mechanism of symptom formation across the various shinkeishitsu types of neurosis, which is called " toraware " and means " to be bound as by some intense preoccupation" [28]. Morita also described shinkeishitsu as "a nervous-prone personality with a hypochondriacal base" [28]. Based on Morita ' s theory, individuals who have a hypochondriacal temperament will develop Taijin-Kyofusho after experiencing an accidental event and becoming highly sensitized [27].…”
Section: Etiology Of Taijin-kyofusho In Morita Therapymentioning
confidence: 99%
“…"Shinkeishitsu" was assessed by a self-administered questionnaire for assessing shinkeishitsu trait [8]. This Japaneselanguage questionnaire consists of 25 yes/no items.…”
Section: Measures Of "Shinkeishitsu"mentioning
confidence: 99%
“…In modern Japanese society, the word "shinkeishitsu" is still a common word, but its meaning represents only nervousness or hysteria. The original meaning of the term "Morita shinkeishitsu" is used as a local diagnosis among Morita therapists, and it remains difficult for people outside this group to understand what Morita shinkeishitsu trulyis [5]. Nevertheless, shinkeishitsu traits can still be found in Japanese workers, as well as in other healthy people.…”
mentioning
confidence: 99%